Creating future-proof cities how to navigate the climate crisis - Murali Ram; Chacko, Rexy Prakash (Areca Books, 2019)
What can you do to help your city adapt to the realities of climate change? This book demystifies the climate crisis and prescribes a localised response, using Penang, Malaysia, as a case study. Policymakers, social entrepreneurs and community practitioners can learn how to accelerate mitigation efforts and improve resilience. This publication cuts through the jargon and serves as a practical guide to individuals, communities and cities to step up action to curb the rise of global temperatures and adapt to future norms. Collective and institutional approaches are urgently needed in the fields of culture, energy, mobility, waste, and land use. Action on these fronts begin with awareness.